2009
DOI: 10.1177/0023830909103165
|View full text |Cite
|
Sign up to set email alerts
|

Optical Phonetics and Visual Perception of Lexical and Phrasal Stress in English

Abstract: In a study of optical cues to the visual perception of stress, three American English talkers spoke words that differed in lexical stress and sentences that differed in phrasal stress, while video and movements of the face were recorded. The production of stressed and unstressed syllables from these utterances was analyzed along many measures of facial movement, which were generally larger and faster in the stressed condition. In a visual perception experiment, 16 perceivers identified the location of stress i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 46 publications
(56 reference statements)
5
79
1
Order By: Relevance
“…van Heuven & Menert, 1996). One possibility is that this asymmetry is driven by the influence of lexical stress on intelligibility: Stressed syllables are produced with more precise and extensive articulation (e.g., Scarborough, Keating, Mattys, Cho, & Alwan, 2009), are more informative about the identity of a word, and are more reliably recognized than unstressed syllables (e.g., Altman & Carter, 1989;Lieberman, 1963;McAllister, 1991;Mehta & Cutler, 1988). Another possible explanation for this asymmetry can be the placement of pitch accents on primary-stressed syllables.…”
Section: Discussionmentioning
confidence: 99%
“…van Heuven & Menert, 1996). One possibility is that this asymmetry is driven by the influence of lexical stress on intelligibility: Stressed syllables are produced with more precise and extensive articulation (e.g., Scarborough, Keating, Mattys, Cho, & Alwan, 2009), are more informative about the identity of a word, and are more reliably recognized than unstressed syllables (e.g., Altman & Carter, 1989;Lieberman, 1963;McAllister, 1991;Mehta & Cutler, 1988). Another possible explanation for this asymmetry can be the placement of pitch accents on primary-stressed syllables.…”
Section: Discussionmentioning
confidence: 99%
“…the face, has led to a new discipline which is sometimes referred to as ''optical phonetics'' (Scarborough et al, 2009). An important problem for this field concerns the relationship between auditory and visual information in human communication.…”
Section: Optical Phoneticsmentioning
confidence: 99%
“…Approaches that base their analyses on spontaneous speech data have often been criticized for using anecdotal evidence. To counter such problems, there have been a number of laboratory studies into the functional use of facial expressions, either by eliciting such expressions from real speakers in specifically designed linguistic or social contexts (Dohen, 2005;Dohen & Loevenbruck, 2009;Dohen, Loevenbruck, Cathiard, & Schwartz, 2004;Krahmer & Swerts, 2007;Scarborough et al, 2009;, or by using an analysis-by-synthesis procedure whereby the effect of specific variations in the face on observers are tested through controlled manipulations of synthetic talking heads (Cassell, Vihjá lmsson, & Bickmore, 2001;Granström, House, & Lundeberg, 1999;Krahmer, Ruttkay, Swerts, & Wesselink, 2002;Krahmer & Swerts, 2004;Pelachaud, Badler, & Steedman, 1996). Such studies showed that facial expressions are indeed functionally relevant as they are exploited to support a broad range of communicative functions (e.g., to highlight important information, or to reveal attitudinal or emotional correlates of speaker utterances).…”
Section: Optical Phoneticsmentioning
confidence: 99%
“…This idea has been later enforced [34]- [37]. Specifically, [34] related eyebrow movement to pitch variations, [35] concluded that stress was best perceived by the visual channel, [36] studied particular articulators involved with stress, and [37] investigated different facial regions. Moreover, facial movements have an influence on the perceived message and its related emotion.…”
Section: Visual Emphasismentioning
confidence: 99%